The Peripheral Inflammatory Response to Alpha-Synuclein and Endotoxin in Parkinson's Disease - White, Alice J.; Wijeyekoon, Ruwani S.; Scott, Kirsten M.; Gunawardana, Nushan P.; Hayat, Shaista; Solim, I. H.; McMahon, H. T.; Barker, Roger A.; Williams-Gray, Caroline H. (Frontiers in Neurology, 2018)
The immune system is activated in Parkinson’s Disease (PD), as evidenced by neuroinflammatory changes within the brain as well as elevated immune markers in peripheral blood. Furthermore, inflammatory cytokine levels in the blood are associated with disease severity and rate of progression. However, the factors driving this immune response in PD are not well established. We investigated cell-extrinsic factors in systemic immune activation by using α-synuclein monomers and fibrils, as well as bacterial toxins, to stimulate peripheral blood mononuclear cells (PBMCs) derived from 31 patients and age/gender-matched controls. α-synuclein monomers or fibrils resulted in a robust cytokine response (as measured by supernatant cytokine concentrations and mRNA expression in cultured cells) in both PD and control PBMCs, similar to that induced by bacterial LPS. We found no PD versus control differences in cytokine production, nor in mRNA expression. Levels of endotoxin within the recombinant α-synuclein used in these experiments were very low (0.2-1.3EU/mL), but nonetheless we found that comparable levels were sufficient to potentially confound our cytokine concentration measurements for a number of cytokines. However, α-synuclein monomers increased production of IL-1β and IL-18 to levels significantly in excess of those induced by low-level endotoxin. In conclusion, this study: (i)highlights the importance of accounting for low-level endotoxin in antigen-PBMC stimulation experiments; (ii)indicates that cell-extrinsic factors may be a major contributor to immune activation in PD; and (iii)suggests that α-synuclein may play a role in inflammasome-related cytokine production in the periphery.